The use of Decasan in the local treatment of chronic inflammatory diseases of the tonsils (Perioperaciina Medicina, 2021)
The local sanitation in 40 patients with recurrent tonsillitis was carried out, using Decasan for washing of the lacunae of the palatine tonsils. Clinical observations and bacteriological studies have shown greater efficacy of Decasan in relation to the main pathogens of the tonsillar lacunae, compared to antibiotic solutions traditionally used for washing. Decasan is a highly effective and safe antiseptic for local treatment of patients with chronic inflammatory diseases of the tonsils, contributing to the restoration of local biocenosis, which is confirmed by an increase in the plaiting of normal microflora from the surface of the tonsillar lacunae.
Keywords: recurrent tonsillitis; microflora; local treatment; antiseptic; Decasan